Aggregation phenomena of a magnetic particle suspension in an alternating magnetic field and the influence on the heat generation effect (Brownian dynamics simulations) - Seiya SUZUKI; Akira SATOH; Muneo FUTAMURA (Nihon Kikai Gakkai ronbunshu, 2018)
We have elucidated the aggregation phenomena in a suspension composed of spherical magnetic particles in an alternating magnetic field by means of Brownian dynamics method. The relationship between aggregate structures and heating phenomena has been discussed using the hysteresis loops of the magnetic field-magnetization curves, which were obtained from Brownian dynamics simulations. A large heating effect is inevitably necessary in applying a magnetic particle suspension to magnetic hyperthermia treatment in the medical engineering field. We here focus on the Brownian relaxation mode of magnetic moments of particles as the factor inducing the heating effect. The main results obtained here are summarized as follows. In the situation where stable chain-like clusters are formed in the field direction, the magnetic particle-particle interaction induces a significant delay for the magnetic moments inclining in the alternating magnetic field direction. These chain-like clusters respond to a change in the magnetic field without collapse and reformation of the clusters, by the magnetic moment of each constituent particle rotating to incline in the field direction. These behaviors of chain-like clusters in an alternating magnetic field exhibit a hysteresis loop with large area in the magnetic filed-magnetization curve, which gives rise to a significantly large heating effect. On the other hand, in the situation where large clusters are formed but these clusters do not strongly tend to incline in the field direction, the area of the hysteresis loop becomes small and therefore a large heating effect cannot be obtained.